Guatemala - Nanne Lippmann, Ingrid (Universidad de Costa Rica, 2020)
Effective literacy programs have, as a common denominator, teachers with specialized training. The study summarized in this article suggests that a significant group of educators in the region do not acquire this level of training and, consequently, do not know what the basic skills of early grade literacy (EGL) are or how they are taught. Pre-service teacher training programs lack evidence-based courses that prepare teachers for this subject. The research, conducted between 2018 and 2019, analyzed the status of pre-service teacher training for the teaching of EGL in a Guatemalan university. A qualitative methodology was applied and data was triangulated from the following sources: (1) the mapping of an EGL pre-service teacher training curricula against a conceptual framework based on evidence on EGL learning and on what teachers-in-training need to learn to be able to teach effectively; (2) interviews with teacher trainers and teachers-in-training; and (3) observations of university classrooms. The results reveal gaps between what the evidence proposes, what the curriculum covers, and the pre-service training that teachers receive. Recommendations are presented for the revision of pre-service teacher training programs and their possible restructuring to better align with current evidence to address some of the identified gaps.